2016
DOI: 10.1128/aac.01739-15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antifungal Activity and Nail Penetration of ME1111, a New Antifungal Agent for Topical Treatment of Onychomycosis

Abstract: Fungal nail infection (onychomycosis) is a prevalent disease in many areas of the world, with a high incidence approaching 23%. Available antifungals to treat the disease suffer from a number of disadvantages, necessitating the discovery of new efficacious and safe antifungals. Here, we evaluate the in vitro antifungal activity and nail penetration ability of ME1111, a novel antifungal agent, along with comparator drugs, including ciclopirox, amorolfine, terbinafine, and itraconazole. ME1111 showed potent anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…In fact, in vitro penetration studies conducted in Franz cell assays using human nail as well as a guinea pig model demonstrated that ME1111 concentrations in the nail following single and/or multiple applications were several orders of magnitude greater than the MFC 50 and MFC 90 determined in this study for three major dermatophytes species causing onychomycosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in vitro penetration studies conducted in Franz cell assays using human nail as well as a guinea pig model demonstrated that ME1111 concentrations in the nail following single and/or multiple applications were several orders of magnitude greater than the MFC 50 and MFC 90 determined in this study for three major dermatophytes species causing onychomycosis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…One case in point is the susceptibility testing of echinocandins against Aspergillus species. It was found that the minimum effective concentration, defined as the lowest concentration with visible morphological changes in growth patterns from filamentous to granular signifying abnormal hyphal growth, correlates better with clinical outcome than with the traditional MIC endpoint for echinocandins against Aspergillus strains (3,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…ME1111 showed potent antifungal activity against Trichophyton rubrum and Trichophyton mentagrophytes (the major etiologic agents of onychomycosis) strains isolated in Japan and reference fungal strains with an MIC range of 0.12 to 0.5 mg/liter and with an MIC 50 and an MIC 90 of 0.5 mg/liter for both (3). ME1111 is a novel antifungal whose small molecular weight enhances its ability to penetrate the nail plate to reach the nail bed where the infection resides.…”
mentioning
confidence: 99%
“…It is highly active in vitro and in vivo against Trichophyton rubrum and Trichophyton mentagrophytes and shows excellent human nail permeability (1)(2)(3)(4). A previous study on its mechanism of action revealed that the molecular target of ME1111 was succinate dehydrogenase (complex II) in the mitochondrial electron transport system (5).…”
mentioning
confidence: 99%